STUDY ON LOGIC AND ARTIFICIAL INTELLIGENCE SUBSETS OF ARTIFICIAL INTELLIGENCE - Lippon Kumar Choudhury (Innovative Research Thoughts, 2022)
The field of computer science known as artificial intelligence (AI) encompasses a wide range of subfields. The purpose of artificial intelligence (AI) is to enable intelligent and autonomous operation of a system. AI gives machines the ability to think for themselves and make their own decisions. Machine Learning is a subset of Artificial Intelligence, while Deep Learning is another subset of Machine Learning. Together, these two types of learning make up AI as a whole. The capacity of a computer programme to study its environment, learn from its experiences, and then respond appropriately by making judgements or carrying out predetermined actions is an example of artificial intelligence. The field of Artificial Intelligence, of which Machine Learning is a part, includes a significant number of already-developed algorithms that may be applied to datasets in order to get relevant insights into the data, etc. These methods have been improved over time to ensure that they are functional when applied to a wide range of datasets, among other things.